Radiation therapy for hepatocellular carcinoma: current status and perspectives from our experience - Wei Jiang; Zhao-chong Zeng (Frontiers Media S.A., 2011)
Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide and is accompanied by a poor prognosis. We had reported that radiation therapy has great potential, in a wide spectrum of primary liver cancers, fromlocal advanced stage of the disease to the more advanced stages, with regional nodal metastases, tumor thrombosis, and for palliation of distant metastases. Following the initial observation that HCC is radiosensitive and with the development of radiation technology, radiotherapy has become a feasible and promising treatment modality for HCC, particularly for advanced forms of the disease. Here, we review the substantial amount of available data on radiotherapy for HCC, report on the current status of this application of radiotherapy, and propose future avenues of research.